Speech Styles Used By Bagas as the Main Character in Pakai Hati the Series - Nathania Edlyn Sosrohartono (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This study aims to find the speech styles used by Bagas as the main character in Pakai Hati The Series when he talked to his colleagues, clients, and supervisors.  In conducting this study, I used the theory of speech styles by Chaer and Agustina (2010), standard Indonesian characteristics by Prihantini (2015) and Kridalaksana (2007), social dimension by Holmes (2017), and status by Brown and Attardo (2005) as the theoretical framework. This study employed a qualitative approach. From the analysis, I found that Bagas used the consultative style, casual style, and intimate style when talking to his colleagues, clients, and bosses. He also used the formal style towards his clients, but he did not use the frozen style when talking to his interlocutors. This study showed that Bagas did not differentiate his speech style merely based on status since there were some other factors that might affect his choice of speech style, namely: habit or personality, type or context of the conversation, and social distance. Keywords: speech styles, status, web series